Meningkatkan Pengetahuan dan Sikap: Efektivitas Emo Demo dalam Praktik Menyusui: Meningkatkan Pengetahuan dan Sikap: Efektivitas Emo Demo dalam Praktik Menyusui - Keya, Rino Tryanto; Prambudi, Aristanto; Cahyani, Fatimah Dwi; Kurnia, Galuh Mega; Widoretno, Anggun Wahyu; Husna, Ahsanu Bil; Bahmid, Moh.; Hermanto, Edi; Noviyanti, Tausyiah Rohmah; Min, Yuliana Purnama Sari; Dewi, Rika Satya; Devy, Shimarti Rukmini; Qomaruddin, Mochammad Bagus; Indawati, Rachmah (Universitas Airlangga, 2025)
Background: Exclusive breastfeeding for the first six months of an infant's life and appropriate complementary feeding are essential for child growth and development. However, the low knowledge and attitudes of mothers and caregivers on Gili Iyang Island pose a challenge in achieving optimal infant feeding practices. Objectives: To determine the effectiveness of emo-demo in improving knowledge and attitudes regarding exclusive breastfeeding and appropriate complementary feeding in Gili Iyang Island. Methods: This pilot study used a pre-test-post-test design with two post-intervention measurements. Respondents consisted of 20 pregnant women and 16 caregivers. The sample was taken by total sampling. Data were analyzed using the Wilcoxon test. Results: The analysis showed a significant increase in the knowledge score of pregnant women after (p=0.008) and 30 days after the emo-demo activity (p=0.008). However, there was no significant change in maternal attitude (p=0.417). In the caregiver, there was a significant increase in knowledge after (p=0.003) and 30 days after the activity (p=0.003) and in the attitude of the caregivers 30 days after the activity (p=0.013). Conclusion: Emo-demo is effective in improving the knowledge of pregnant women and their caregivers regarding exclusive breastfeeding and appropriate complementary feeding. However, the effect on participants' attitudes requires additional approaches for more optimal results.